2007
DOI: 10.1289/ehp.10216
|View full text |Cite
|
Sign up to set email alerts
|

Nanosize Titanium Dioxide Stimulates Reactive Oxygen Species in Brain Microglia and Damages Neurons in Vitro

Abstract: BackgroundTitanium dioxide is a widely used nanomaterial whose photo-reactivity suggests that it could damage biological targets (e.g., brain) through oxidative stress (OS).ObjectivesBrain cultures of immortalized mouse microglia (BV2), rat dopaminergic (DA) neurons (N27), and primary cultures of embryonic rat striatum, were exposed to Degussa P25, a commercially available TiO2 nanomaterial. Physical properties of P25 were measured under conditions that paralleled biological measures.FindingsP25 rapidly aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
281
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(296 citation statements)
references
References 42 publications
12
281
1
2
Order By: Relevance
“…Extensive particle accumulation in conjunction with iron toxicity post-degradation is the likely pathological correlate of MP toxicity in these cells [47]. By contrast, in the other cell types, particles appeared to be relatively stable morphologically with negligible associated toxicity.…”
Section: Discussionmentioning
confidence: 91%
“…Extensive particle accumulation in conjunction with iron toxicity post-degradation is the likely pathological correlate of MP toxicity in these cells [47]. By contrast, in the other cell types, particles appeared to be relatively stable morphologically with negligible associated toxicity.…”
Section: Discussionmentioning
confidence: 91%
“…TiO 2 is one of most frequently used materials in commercial products, e.g., cosmetics and dental care, 66 and concerns regarding the effects of TiO 2 nanoparticles on human health, including neurological damage, 67,68 have been raised. However, the fate of TiO 2 nanoparticles upon exposure to the human BBB has not been clearly defined to date.…”
Section: Uptake and Transcytosis Of Human Serum Albumin And Transferrmentioning
confidence: 99%
“…Serum levels of immunoglobulin G, TNF-α, CRP and IL-6 were also elevated. Some studies have shown that TiO 2 nanoparticles could increase the reactive oxygen species, which in turn depleted cellular antioxidants (Long et al 2007;Lu et al 2008;Park et al 2008;Wang et al 2008;Mallik et al 2011). Adverse biological effects exerted by NPs is thought to be caused by the oxidative stress (Donaldson et al 2001;Gurr et al 2005;Nel et al 2006) and results in DNA oxidation in the heart, DNA strand breaks, inflammation and even cell necrosis (Sheng et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It was thought that TiO 2 -NPs were non-toxic mineral (Sager et al 2008). However, many studies suggested that titanium dioxide nanoparticles could be more toxic than their original materials (Long et al 2007;Zhao Jet al 2009;Zhao Jet al 2011;Magaye and Zhao 2012;Liu K et al 2013). The exposure to nanoparticle can be either accidentally due to occupational exposure, or intentionally through different routs such as nose by inhalation, mouth by ingestion, skin contact or intravenous injection (Zhu et al 2012;Khan and Maskat 2014).…”
Section: Introductionmentioning
confidence: 99%